How are e-leadership practices in implementing a school virtual learning environment enhanced? A grounded model study. (June 2017) - Chua, Yan Piaw; Chua, Yee Pei
Abstract: E-leadership is defined as a social influence process mediated by information and communication technology to produce change in behavior and performance with individuals and groups in an organization. This study investigates e-leadership practices among users of a school virtual learning environment. It was performed in two stages. First, semi-structured interviews with school administrators, teachers, students, parents and school software experts were conducted. The qualitative data collected from the interviews were coded and analyzed using open and axial coding procedures. As a result, an e-leadership model emerged from the data that consisted of eight themes: e-leadership quality with seven core factors, namely, readiness, practices, strategies, support, culture, needs and obstacles. Second, the validity and reliability of the model were further ascertained with a quantitative survey study involving 320 school administrators. The findings of this study established a grounded model for e-leadership practices in schools. Highlights: This study investigated e-leadership practices among users of a school VLE. An e-leadership model emerged from the data that consisted of eight themes. The validity and reliability of the model were further ascertained with a survey study. The study established a grounded model for e-leadership practices in schools.